The Role of Takaful Insurance companies in Covering the Risk of Islamic Financial Institutions - بيراز نوال (Finance and Business Economies Review, 2021)
This research paper aims to clarify the types of risks that Islamic financial institutions may face, as well as highlighting the role played by the insurance institutions of solidarity in covering the risks of Islamic financial institutions. This is in order to enhance its activities and business based on the insurance services provided to Islamic banks, Islamic investment funds and the Islamic stock market. This study concluded that Islamic financial institutions are exposed to a number of risks when exercising their functions and employing their funds. Which makes it resort to the insurance institutions of solidarity in order to cover these risks and reduce them. The existence of insurance institutions of solidarity today is very important due to the insurance services they provide to cover most of the risks and decrease their effects in the event of their occurrence